(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
In this article the author reveals the specifics of axiological approach to modern problems of communication with the help of fundamental philosophical theories analysis. In the center of the study are such concepts as socio-philosophical reflection, intersubjectivity, alienation, personalism and ideal communicative community. These concepts have become the starting points of 20th century philosophy in the study of human being’s existential nature. The moral priorities of the philosophical theories’ founders were aimed against the monological concept of communication, the use of human being and various manipulative techniques directed solely for profit. According to the philosophers, the value basis of communication is in the process of building a true dialogue, where each of its participants acquires an ideal relationship and comes to an understanding of the other. The theories that contribute to the return of man to his true moral purpose are becoming particularly relevant in connection with the cultural world’s unification, the globalization process, and the humiliation of an individual as an object of virtue. The construction of an ideal communicative group becomes possible when the participants of communication overcome their own subjective attitudes and create mutual rational motivation. The considered theories call for such universal human values as love, care, respect, honesty, freedom, justice, spirituality, truth, and humanity. According to the philosophers, appeal to these values in the process of communication can lead a person out of the widespread alienation and unlock the destructive existential circle of modern human being, constructed of vices. Keywords: existentialism; values; alienation; interaction; dialogue; ethics; morality; communicative group; axiology; human; society.